PENGARUH TERAPI KOMPRES HANGAT TERHADAP PENURUNAN NYERI SENDI OSTEARTRITIS PADA LANSIA - italia italia (LPPM STIKes Mitra Adiguna, 2022)
The World Health Organization (WHO) shows that in the United States the incidence of osteoarthritis based on doctor's diagnosis and symptoms has reached 24.7%. Joint pain is one of the trigger factors and the main complaints that arise in patients with osteoarthritis. The purpose of this study was to determine the effects of warm compresses on osteoarthritis joint pain in the elderly at the Harapan Kita Elderly Social Institution KM.5 Palembang in 2021. Warm compresses are a non-pharmacological measure used to reduce joint pain. Its scope is gerontic nursing. The research method/design used was an experiment with a One Group Pretest-Posttest Design test approach and the research sample was 25 elderly people. The results obtained from most of the respondents' joint pain before doing warm compress therapy were moderate pain as many as 14 people (56%) and univariate analysis of the majority of respondents' joint pain after doing warm compress therapy was mild pain as many as 16 people (64%) and bivariate analysis Wilcoxon statistical test obtained p value = 0.000 <0.05, it means that there is an effect of warm compress therapy on reducing osteoarthritis joint pain in the elderly at Harapan Kita Elderly Social Institution Palembang. Suggestions to health workers, especially those in elderly social institution, are expected to be able to suggest or teach the elderly how to do warm compresses to reduce the joint pain they feel. Keywords : warm compresses, joint pain